2018
DOI: 10.1093/ije/dyy064
|View full text |Cite
|
Sign up to set email alerts
|

Preterm infants have distinct microbiomes not explained by mode of delivery, breastfeeding duration or antibiotic exposure

Abstract: Preterm infants had distinct gut microbiome composition and function in the early postnatal period, not explained by factors more common in preterms, such as shorter breastfeeding duration, more antibiotics or caesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 56 publications
4
63
0
11
Order By: Relevance
“…Our early study demonstrated that the intestinal microbiome samples from preterm infants up through 5 weeks of life cluster distinctly from those of a full‐term breastfed infant and that the microbial patterns converge toward those of full‐term breastfed infants only at or after 6 weeks of life (Claud et al, ). We and others further demonstrated that the microbiome of the preterm infant is characterized by low diversity and high interindividual variation (Claud et al, ; Dahl et al, ; Kurokawa et al, ; Moles et al, ) with succession of bacterial classes from Bacilli to Gammaproteobacteria to Clostridia (Itani et al, ; Korpela et al, ; La Rosa et al, ; Underwood & Sohn, ). Postmenstrual age (PMA), which is the gestational age (GA) plus age of life, has been reported as the major driver in the development of the microbiome for preterm infants specifically for the rate of the assembly, with the slowest rate found in the most premature of infants (between 25 and 30 weeks of PMA; Korpela et al, ; La Rosa et al, ).…”
Section: Factors Affecting the Assembly Of Neonatal Gut Microbiotamentioning
confidence: 77%
See 3 more Smart Citations
“…Our early study demonstrated that the intestinal microbiome samples from preterm infants up through 5 weeks of life cluster distinctly from those of a full‐term breastfed infant and that the microbial patterns converge toward those of full‐term breastfed infants only at or after 6 weeks of life (Claud et al, ). We and others further demonstrated that the microbiome of the preterm infant is characterized by low diversity and high interindividual variation (Claud et al, ; Dahl et al, ; Kurokawa et al, ; Moles et al, ) with succession of bacterial classes from Bacilli to Gammaproteobacteria to Clostridia (Itani et al, ; Korpela et al, ; La Rosa et al, ; Underwood & Sohn, ). Postmenstrual age (PMA), which is the gestational age (GA) plus age of life, has been reported as the major driver in the development of the microbiome for preterm infants specifically for the rate of the assembly, with the slowest rate found in the most premature of infants (between 25 and 30 weeks of PMA; Korpela et al, ; La Rosa et al, ).…”
Section: Factors Affecting the Assembly Of Neonatal Gut Microbiotamentioning
confidence: 77%
“…Postmenstrual age (PMA), which is the gestational age (GA) plus age of life, has been reported as the major driver in the development of the microbiome for preterm infants specifically for the rate of the assembly, with the slowest rate found in the most premature of infants (between 25 and 30 weeks of PMA; Korpela et al, 2018;La Rosa et al, 2014). A recent study corroborated this finding, demonstrating that GA is the dominant factor in microbiome assembly, independent of confounders such as mode of delivery, breastfeeding duration, and antibiotic exposure with preterm infant microbiota demonstrating lower diversity and more Proteobacteria and Enterococcus compared with full-term infants at 10 days postpartum (Dahl et al, 2018). However, the difference between preterm and term infants in bacteria diversity was not observed at 4 or 12 months postpartum, consistent with our study observing a shift of preterm microbiome to full-term infant microbiome patterns at 6 weeks of age and later (Claud et al, 2013) and confirming an age-dependent maturation of the preterm infant microbiome.…”
Section: Initial Bacterial Colonization and Successionmentioning
confidence: 78%
See 2 more Smart Citations
“…Dobbler et al () identified low microbial diversity and chaotic succession for infants who developed NEC. The Norwegian Microbiota Study reported duration of NICU care to be a significant mediator of diversity, but not breastfeeding or history of antibiotic use (Dahl et al, ). After adjusting for antibiotic and breastmilk exposure and delivery mode, Chernikova et al () found differences in diversity based upon birth gestational age, with extremely preterm infants having less diversity than moderate–late preterm infants (Chernikova et al, ).…”
Section: Introductionmentioning
confidence: 99%